Magnetic resonance imaging evaluation of intervertebral disc injuries can predict kyphotic deformity after posterior fixation of unstable thoracolumbar spine injuries. Issue 28 (July 2018) - Kanezaki, Shozo; Miyazaki, Masashi; Ishihara, Toshinobu; Notani, Naoki; Tsumura, Hiroshi
Abstract : Abstract: The aim of the present study is to identify factors correlated with kyphotic deformity after thoracolumbar spine injuries. We performed a retrospective case–control study with data from thoracolumbar spine fracture patients who were treated with posterior spinal fixation. Patients with a follow-up period shorter than 6 months and who experienced low-energy trauma were excluded. Intervertebral disc injuries (IDIs) were graded from 0 to 3 upon admission in accordance with Sander's classification of traumatic intervertebral disc lesions. Vertebral wedge angles (VWAs) and local kyphosis angles (LKAs) were also measured. Patients were allocated to kyphosis and control groups if they had LKA correction losses of ≥10° and <10°, respectively. Forty-eight patients followed over a median period of 25 months were included. The median correction loss at the site of the injured vertebral body was 2.0°. The median LKA correction loss was 9.0°. Twenty-three and 25 patients were allocated to the kyphosis and control groups, respectively. Univariate analysis revealed that the median age was significantly lower in the kyphosis (35 years) than control group (56 years). The level of injury and IDI severity also significantly differed between groups, with a significantly greater proportion of more severe IDI cases in the kyphosis than control group. Finally, significantly more patients in kyphosis group underwent fusion (kyphosis, 19 vs control, 13) and implant removals (kyphosis, 19 vs control, 10). Multiple regression analysis revealed that IDI severity according to Sander's classification ( P  = .005; odds ratio, 5.263; 95% confidence interval [CI], 1.637–16.927) and implant removal ( P  = .011; odds ratio, 7.980; 95% CI, 1.603–39.728) were significantly associated with kyphotic deformity. IDI severity at initial magnetic resonance imaging (MRI) evaluation and implant removal are associated with kyphotic deformity after posterior fixation of thoracolumbar spine injuries. Thus, initial MRI evaluation of IDIs could be used to predict of recurrent kyphosis.